Ibn Sina Dan Pemikiran Teori Emanasi - Baharuddin, Ahmad (Jurnal Adabiyah, 2015)
Abu Ali Husain ibn Abdullah ibn Hasan ibn Ali ibn Sina has surpassed the fame of al-Farabi and al-Kindi. He was born in a state government that is still unstable. He grew to be a scientist with various areas of expertise. Among them: philosophy, logic, and medicine. Avicenna is called in the West known as the doctor goes beyond his fame as a philosopher. They spread them âthe Prince of the Physicians and in the Islamic world called al-Shaikh al-Rais / main leaders of the philosophers. In philosophy he also has to understand emanations and common-sense to him is attached. The realization he divided into three parts, obligatory, possible and impossible. His philosophy of life and be more detailed and perfect from the philosophy of al-Farabi. Ibn Sinas thought about the prophetic explain that the prophet was a human being is the most superior, superior to the philosopher as the Prophets had actual perfect sense without training or study hard, while philosophers get with effort and difficulty.